Bourdieu, language-based ethnographies and reflexivity putting theory into practice - Grenfell, Michael 1953-; Pahl, Kate (Routledge, 2019)
Offering a unique and original perspective on Bourdieu, language-based ethnographies,and reflexivity, this volume provides a nuanced, in-depth discussion of the complex relationship between these interconnected topics and their impact in real-world contexts. Part I opens the book with an overview of the historical background and development of language-based ethnographic research and Bourdieu's work in this space. Part II presents a series of case studies that highlight a Bourdieusian perspective and demonstrate how reflexivity impacts language-based ethnography. In each study, Bourdieu's conceptual framework of reflexively-informed objectivity examines the ways in which the studies themselves were constructed and understood. Building on Parts I and II, the concluding set of chapters in Part III unpacks the messiness of the theory and practice of language-based ethnography, and provides insights into what reflexivity means for Bourdieu and in practical contexts. Arguing for a greater reflexive understanding in research practice, this volume sets an agenda for future literacy and language research
Description based on print version record and CIP data provided by publisher
Keywords: Bourdieu, Pierre / 1930-2002; Language and culture; Literacy / Social aspects; Sociolinguistics